Evaluation of trichiasis surgeons' performance in selected trachoma endemic African countries - Ofoegbu, Olubukola Oyinade (Division of General Surgery, 2022)
Purpose: Elimination of trachoma-related blindness requires addressing not only issues of trichiasis surgery availability and accessibility, but also quality. To improve surgeon performance, programmes undertake surgeon audits to identify surgeons needing re-training, reasons for poor outcomes, and actions to optimise surgical outcomes. This study aims to determine the frequency and associated factors of audits conducted in selected countries and factors associated with failed audits. Methods: A multicentric study was conducted as a secondary data analysis of surgeon audit results for eight African countries. Stata® was used to generate results for chi-square tests for association, odds ratio and 95% confidence intervals between independent samples for categorical variables and one-way ANOVA tests for continuous variables. Results: The study included 561 trichiasis surgeons and 193 (34.4%) had an audit. Dedicated eye care workers were more likely to have an audit (p<0.001) compared to general health workers. Among audited surgeons, 29 (15%) failed and were recommended for re-training. Surgeons using posterior lamellar tarsal rotation (PLTR) surgery (59.8%) and those trained more recently (mean 4.2 years) were more likely to pass the audit. Conclusion: Although surgeon audits are considered a routine part of programme activities in trachoma endemic countries, too few audits are being undertaken. Further research is needed to learn why surgeons practicing PLTR surgery and those trained more recently are more likely to pass their audit. To improve surgical outcomes, programmes must not only focus on surgical volume but carry out surgeon audits and use the audits to make programme decisions.